Integral Agritourism Strategy Through Non-Agricultural Tourism–Coffee Agribusiness Integration (Evidence from Latimojong Village Indonesia) - Abd Rahim; Sri Nur Qadri; Putriani Putriani (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Rural tourism development in agricultural regions requires innovative integration strategies to enhance local economic sustainability. However, most agritourism models still emphasize farm-based attractions, limiting integration opportunities for regions dominated by non-agricultural tourism. This study aims to propose an alternative agritourism development model by integrating non-agricultural tourism attractions with coffee agribusiness, referred to as integral agritourism, in Latimojong Village, Indonesia. A qualitative case study approach was employed using SWOT analysis based on in-depth interviews with 21 key stakeholders, including coffee farmers, tourism actors, academics, and visitors. The results indicate that the integration strategy is positioned in Quadrant I (growth strategy), reflecting strong internal capabilities and favorable external opportunities. The main strengths include superior coffee quality and strategic access to tourist markets, while significant opportunities arise from tourism-based branding and market expansion. In conclusion, integral agritourism extends conventional agritourism concepts by embedding agricultural products within existing tourism experiences and offers a replicable strategy for integrated rural development and sustainable local branding.